A Compact Reaction Mechanism of Methane Oxidation at High Pressures. (March 2018) - Zhukov, Victor P.; Kong, Alan F.
A skeletal methane kinetic mechanism is developed for conditions relating to the combustion of undiluted methane–oxygen mixtures at high pressures. The new skeletal mechanism is based on the detailed mechanism of oxidation of alkanes by Zhukov (2009). The skeletal model has been created by eliminating unimportant species and reactions from the detailed mechanism. The reduction technique is based on the reaction path and sensitivity analyses. They allow one to determine the reactions and species that play important roles in combustion in rocket combustion chambers. The skeletal mechanism consists of 23 species and 51 reactions. The final and intermediate versions of the skeletal mechanism are compared with the parent detailed mechanism, with other reduced kinetic models and with experimental data on the ignition of methane at high pressures. This comparison shows that the developed skeletal mechanism has a better performance than other kinetic mechanisms in terms of accuracy and required computational power.